Disordered eating and eating disorders in male elite athletes: a scoping review - Karrer, Y.; Halioua, R.; Mötteli, S.; Iff, S.; Seifritz, E.; Jäger, M.; Claussen, M. C. (BMJ Open Sport & Exercise Medicine, 2020)
Background Eating disorders (ED) and disordered eating (DE) among male elite athletes share some of the characteristics seen in female elite athletes and the population, but also exhibit some key differences.